DNA methylation pattern in high-grade cervical intraepithelial neoplasia and cancer revealed by genomewide methylation analysis of cervical DNA - García, D. Adriana (2017)
Cancer of the uterine cervix is caused by a subset of oncogenic human Papillomavirus (HPV)-types with mucosal tropism. Besides the known effects of the viral oncoproteins on cellular functions there is evidence suggesting that cervical carcinogenesis involves epigenetic changes in the host DNA. In this study, we have examined the global promoter methylation profile associated with progression to cervical cancer at wide genome scale. The methylation pattern of nearly 14,000 genes was analyzed in cervical swabs at different stages of cervical carcinogenesis: low-grade cervical intraepithelial neoplasia (CIN I and II), high-grade CIN (CIN III) and invasive cancer, as well as healthy individuals. Unsupervised analysis (Hierarchical Clustering) identified two groups: A) healthy, CIN I and CIN II; and B) CIN III/cancer. Supervised T-Test analysis showed 1069 promoter regions hypermethylated and 85 hypomethylated in CIN III/cancer compared to CIN I/CIN II and healthy samples (p<0.0001). Overall, the differentially methylated genes act in transcription, cell cycle, apoptosis and cell adhesion pathways. Of the hypermethylated genes, 132 (12.3%) were down-regulated in a matched cervical cancer group. In turn, only 4 (4.7%) of the hypomethylated genes were overexpressed in that group.